2018
DOI: 10.17675/2305-6894-2018-7-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water-soluble monomers on the corrosion protection ability of chromium coatings obtained from Cr(III)-based solutions

Abstract: The effect of water-soluble electropolymerizable monomer additives in Cr(III) sulfateoxalate electrolytes on the corrosion-electrochemical behavior of chromium coatings and their ability to protect the steel support is studied. The additives into the Cr(III) sulfateoxalate electrolytes were caprolactam, aniline, and acrylamide. The XPS technique showed that both the surface and bulk layers of chromium coatings obtained from electrolytes with additives contain products of chemical or electrochemical conversions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…X-Ray fluorescence analysis showed that carbon and oxygen are additionally included in the Co-Cr-W coating. The presence of carbon in the coating is characteristic of the electrodeposition of chromium and its alloys from electrolytes based on trivalent chromium compounds [12][13][14][15]. The source of carbon is apparently dimethylformamide.…”
Section: Resultsmentioning
confidence: 99%
“…X-Ray fluorescence analysis showed that carbon and oxygen are additionally included in the Co-Cr-W coating. The presence of carbon in the coating is characteristic of the electrodeposition of chromium and its alloys from electrolytes based on trivalent chromium compounds [12][13][14][15]. The source of carbon is apparently dimethylformamide.…”
Section: Resultsmentioning
confidence: 99%